Declutter your life : how outer order leads to inner calm - Hasson, Gill (Wiley, 2018)
With plenty of ideas, advice, tips and techniques to help you, this book explains how the principles and steps taken to clear and simplify your living space can improve not just your home but also other aspects of your life; your work, relationships and general wellbeing. --